Territorial resilience the third dimension of agroecological scaling: Approximations from three peasant experiences in the South of Mexico. Issue 7 (14th September 2019) - Guzmán Luna, Alejandra; Ferguson, Bruce G.; Schmook, Birgit; Giraldo, Omar Felipe; Aldasoro Maya, Elda Miriam
ABSTRACT: In this paper we explore the depth dimension of agroecological scaling. Through interviews, focus groups and participant observation, we explore the link between agroecology and the recovery and maintenance of ecosystem functions through three case studies in peasant communities in southern Mexico. These communities have contrasting ecological, social and historical contexts, but all engage in autonomous initiatives for agroecology and nature protection. We found that agroecology deepens when rooted in a cultural matrix of peasant identity, spiritual values, and local institutions.